2019
DOI: 10.1097/jcn.0000000000000553
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Perceptions of Self-efficacy and Quality of Life in Patients Having Coronary Artery Bypass Grafting and Their Family Caregivers

Abstract: Background: Self-efficacy is a critical factor of quality of life in patients who undergo coronary artery bypass grafting (CABG) as well as their family caregivers. However, there is lack of knowledge about whether patients' self-efficacy and caregivers' perceptions of patient self-efficacy are associated with quality of life in two member dyads. Objectives: To compare self-efficacy and quality of life between patients and family caregivers and to examine whether patients' and caregivers' perceptions of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Our results for differences in mental health (outcomes) between the patients and caregivers revealed their scores were similar; a finding which is consistent with prior research [40,60,61]. The EUROACTION study also showed that couples often share similar ratings of health-related quality of life [49].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results for differences in mental health (outcomes) between the patients and caregivers revealed their scores were similar; a finding which is consistent with prior research [40,60,61]. The EUROACTION study also showed that couples often share similar ratings of health-related quality of life [49].…”
Section: Discussionsupporting
confidence: 91%
“…The SF-12v2 scores were calculated following the norm-based scoring algorithm, using weights derived from confirmatory factor analysis [32]. The measure has demonstrated good validity and reliability [31,33,34], and it has been used in studies of cardiac patients [2,[35][36][37][38][39], and patientcaregiver dyads [40][41][42]. Cronbach's alpha for the PCS was 0.77 for patients and 0.89 for caregivers; and the MCS was 0.81 for patients and 0.91 for caregivers.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Analysis of all 9 BSI sub-scales revealed the patients' and caregivers' scores were not statistically significantly different, except for somatisation (i.e., greater distress arising from perspectives of bodily dysfunction), which was not unexpectedly higher in patients. This finding is consistent with earlier studies that found patient and caregiver congruence in mental health and wellbeing [34,84,85]. Compared to previous research [46,47], the patients' somatisation and obsession-compulsion scores were high, indicating greater emotional distress arising from perspectives of bodily dysfunction, and thoughts, impulses and actions that were unremitting and irresistible.…”
Section: Discussionsupporting
confidence: 90%
“…After the CABG, the PCS and MCS scores were most strongly affected by self-efficacy, and this finding is in agreement with the results of previous studies and research which indicated that self-efficacy is a key factor that determined the post-CABG HRQOL in patients with CAD 23 and heart failure 31 . Recovery and adaptation following CABG are influenced by the patient's physical condition and treatment, as well as by their perception of their own capability to organize and execute the actions that are required to achieve their goals 28 , 32 , 33 . This is because self-efficacy helps CAD patients recognize risk factors, thereby enhancing their self-care compliance, such as through positive lifestyle changes 27 , 28 , confidence in treatment, and psychological resilience 29 .…”
Section: Discussionmentioning
confidence: 99%